Equilibrium studies on adsorption of bovine serum albumin (BSA) using PVDF membrane (Immobilon-PSQ): article - Huzaini, Nurul Nabila; Ideris, Norhidayah (2018)
Polyvinylidene fluoride (PVDF) is a semi-crystalline structure that is an outstanding and distinctive polymer that widely used as a membrane material [1]. A study on the capability and characteristic of PVDF membrane [2] to adsorpt protein is done due to the its outstanding uses in development of biosensor. Studies on the characteristic of PVDF membrane in term of morphology and polymorph as well as equilibrium adsorption of BSA on PVDF membrane is carried out. In this study, the initial cocentration of protein is varied in the range of 0.25 mg/L , 0.5 mg/L , 0.75 mg/L , 1.0 mg/L and 1.25 mg/L. Characteristic of PVDF membrane such as the pore size, porosity, water contact angle and functional group by using Field emission scanning electron microscopy (FESEM), VCA-3000S water surface analysis (AST, USA), Fourier transformation infrared spectroscopy (FTIR) respectively and also weighing scale. The concentration of BSA adsorbed is measured at λ = 562 nm by using UV-vis spectrophotometer. The linear equllibrium isotherm model used to obtain the amount of BSA bind to the membrane are Langmuir and Freundlich Isoterm.